Study of compression behaviour of 3D-printed honeycomb based sandwich structured composites - Jayashankar Dhileep Kumar (2017)
The aim of this research is to study the compressive response of the 30 printed honeycomb based sandwich structure. Four different kinds of sandwich structures were designed and 30 printed by the photo polymerisation process. Analysis was done with the experimental setup and numerical data. Out-of-plane crushing behaviour have been investigated for four structures, namely vertical pillar corrugated sine wave structure (VPCS), vertical pillar cotTugated trapezoidal structure (VPCT), icosahedron structure and kagome structure. The designed specimens were printed using Pro jet 5500X machine with different combinations of ABS (CR-WT) and rubber (CF-BK) series, and tested to determine the best combination of the composites in response to the compression behaviour. Material combinations like AA, AB 100, AB200 & B 1008200 are generated for the designs from visijet composite material for the Projet 5500X machine. Optimization was can·ied for two designs by incorporating weight optimization method with the help of Solid Works software and further proceeded for manufacturing and testing for the optimized designs. In another case, optimum material combination was found out and applied for two corrugated designs to validate the performance behaviour between the composite combinations. Out-of-plane compression test was carried out with the I 00 kN Universal testing machine and the results were plotted for detailed comparison between designs as well as material combination of composites. As a result, the top composite combination was found out and concluded for effective use of it for appropriate applications based on the requirements.